Modeling of the Co-Mn-Br catalyzed liquid phase oxidation of p-xylene to terephthalic acid and m-xylene to isophthalic acid. (15th March 2021) - Lyu, Quanming; Dong, Jian; He, Renchu; Sun, Weizhen; Zhao, Ling
Highlights: A new kinetic model incorporates the catalyst proposition and concentration. The parameters α and β reflect the catalyst reactivity and can be transferrable. The third parameter γ is much related with the methyl reactivity of PX or MX. The predicted reactivity of PX to MX is pretty close to the Hammett equation. Insights into the modeling of the catalytic oxidation of hydrocarbon. Abstract: The current kinetics of PX or MX oxidation in liquid phase failed to incorporate the effect of the proposition and concentration of Co-Mn-Br ternary catalyst, although they play a significant role in the oxidation rate and selectivity. In this work, based on the catalytic mechanism of hydrocarbon oxidation and collision theory, a three-parameter model containing the catalyst proposition and concentration was developed. The reliability of this model was confirmed by comparing experimental data at different catalyst concentrations and ratios. The parameters α and β are related to the reactivity of Co and Mn ions respectively, and they are transferrable between PX and MX oxidation. However, the parameter γ is only related to the methyl reactivity of PX or MX with Br . The predicted relative reactivity of PX to MX is close to the famous Hammett structure-reactivity relationship.